2015
DOI: 10.1111/bju.12985
|View full text |Cite
|
Sign up to set email alerts
|

A novel interface for the telementoring of robotic surgery

Abstract: ObjectiveTo prospectively evaluate the feasibility and safety of a novel, second-generation telementoring interface (Connect TM ; Intuitive Surgical Inc., Sunnyvale, CA, USA) for the da Vinci robot. Materials and MethodsRobotic surgery trainees were mentored during portions of robot-assisted prostatectomy and renal surgery cases. Cases were assigned as traditional in-room mentoring or remote mentoring using Connect. While viewing two-dimensional, real-time video of the surgical field, remote mentors delivered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 27 publications
0
46
0
1
Order By: Relevance
“…4a). If proctors moved in two dimensions, which closely parallels the type of instruction from telestration on the touch screen or through da Vinci Connect [8], the z -direction excursions would not differ significantly from zero (or the x - and y -directions). Therefore, when given the ability to provide instruction to trainees in the same rich 3D environment, proctors consistently utilized 3D movements.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4a). If proctors moved in two dimensions, which closely parallels the type of instruction from telestration on the touch screen or through da Vinci Connect [8], the z -direction excursions would not differ significantly from zero (or the x - and y -directions). Therefore, when given the ability to provide instruction to trainees in the same rich 3D environment, proctors consistently utilized 3D movements.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies on both intra- and inter-hospital telementoring, we found that proctors frequently expressed a desire for 3D viewing and 3D telestration by the proctor [8, 9]. Thus, remote proctoring can be improved beyond 2D so that the trainee and proctor share a more similar view of the operative field.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several other successful telementoring training events have been reported from across the world. [545556]…”
Section: Modalities For Surgical Educationmentioning
confidence: 99%
“…The study published by Shin et al. in this issue of BJUI is a technical proof of concept study and is an important first step to realising the potential of robotic networks. The study describes the application of Connect on a local area network (LAN), which is a network that interconnects computers in a limited geographical area such as a hospital, whereas a wide access network (WAN) is a computer network spanning regions, countries or even the world.…”
mentioning
confidence: 99%